Kualitas Pelayanan Pengelolaan Sampah Masyarakat di Kota Ambon - Marno Wance (PT FORMOSA CENDEKIA GLOBAL, 2022)
The city of Ambon is a center for the development of education, services, trade and the center of government which can lead to an increase in waste disposal which is increasingly varied and increasing. So that the Ambon City Government issued Regional Regulation Number 18 of 2015 as an umbrella law for managing waste, namely when waste is collected, transported to the Final Disposal Site (TPA) so that good and fast waste management is needed. This research was conducted to measure the quality of community waste management services in Ambon City. The research method used is descriptive quantitative with a random sampling approach to 87 research respondents. The conclusions of the study are (1). indicators of socialization of Regional Regulation No. 18 of 2015 Ambon City Government has not yet had incentives to disseminate information to the public. (2). The indicator of the quality of public facilities and infrastructure services assesses that the City Government has not been maximal in preparing the quality of garbage disposal sites in Ambon City.